Die aval in die Suid-Afrikaanse wisselreg - Van Schalwyk, Johan Hendrie (University of the Free State, 1969)
Abstract not available
Keywords: Commercial law -- South Africa; Bail -- South Africa; Roman-Dutch law; Dissertation (LL.B. (Law))--University of the Free State, 1969